Pemanfaatan Sumber Daya Alam Hayati Sebagai Objek Wisata Dan Tingkat Kesejahteraan Masyarakat Sekitar Lokasi Wisata - Dian Minasari Siregar, Sri Ramadhani, Annio Indah Lestari Nasution (Journal Economy and Currency Study (JECS), 2021)
Tourism activities are activities that involve various interests (multi-sectoral) and are closely related to global economic developments. In addition, tourism is an activity that relies on the utilization of the potential of the natural resources that exist in each object and tourist attraction while still guided by balance and preservation (without destroying the natural potential they have). In this paper, it is about the use of biological natural resources as a tourist attraction and the level of welfare of the community around the Pematang Johar tourist site. Therefore, the purpose of this study is to identify the physical carrying capacity and potential of rice field tourism in supporting tourism activities and find out whether the construction of rice field tourism facilities is able to provide welfare for the community around tourist sites. This study uses a type of field research (Field Research) with a research nature this is descriptive qualitative. The results of the study indicate that the physical carrying capacity and potential of rice field tourism in supporting tourism activities are human resources who play an important role in managing tourist villages, adequate facilities and infrastructure such as worship facilities and public toilets as well as infrastructure to the location is also quite good with good road access. And good promotion. The construction of rice field tourism facilities is able to provide welfare for the people around the tourist sites, which can be seen from the number of jobs and reducing unemployment in the tourist village of Pematang Johar itself, which is evident from the increasing economy of the income of the people around the location and the growing socio-cultural value.